A Compact Laser Imaging System for Concurrent Reflectance Confocal Microscopy and Laser Doppler Flowmetry - Alireza Mowla; Thomas Taimre; Yah Leng Lim; Karl Bertling; Stephen J. Wilson; Tarl W. Prow; Aleksandar D. Rakic (IEEE Photonics Journal)
We propose a compact laser feedback interferometry imaging system for concurrent reflectance confocal microscopy and laser Doppler flowmetry. This system acquires both confocal reflectance and Doppler signals in a confocal architecture to image dynamic turbid media with higher contrast than a system operating in either modality and is coherent in nature. In a confocal optical configuration, reflectance confocal microscopy provides information about scattering from within a small volume centered around the focal point of the confocal system, and laser Doppler flowmetry provides information about the velocity of moving scatterers within the same volume. Raster scanning the sample enables the concurrent creation of two images, containing independent information, from a well-specified depth within the sample. Concurrent spatial mapping of these independent sensing modalities affords improvement in the capability of the imaging system by obtaining additional information from both morphological and functional features of the dynamic turbid medium at depths penetrable by near-infrared lasers. We realize the idea using a laser feedback interferometry imaging system scanning a microfluidic channel that contains a dynamic turbid medium. We show the effectiveness of this integrated imager quantitatively through the improvement of the signal-to-background ratio of a combined (multiplication) image.